College students' dining expectations in Cyprus - Pribic, Jovana; Zopiatis, Anastasios (My University, 2007)
Abstract: Purpose – The primary purpose of the study is to investigate college students' dining expectations and define the factors that shape their dining choices. In addition, the study investigates whether gender, ethnic origin, prior food and beverage working experience, spending habits and dining frequency influence students' dining expectations. Design/methodology/approach – A quantitative questionnaire was developed and randomly administered to college students all over Cyprus. With the utilization of both descriptive and inferential statistics the authors addressed a number of research questions that aim to clarify college students' dining behaviour. Findings – The research reliably measured college students' dining expectations and dining decisions in the Cyprus specific environment. Overall cleanliness, employees' attitude and quality of menu items were the most important factors influencing college students' dining choices. Reliability and responsiveness were ranked as the top dining expectations of college students. In addition, of value to industry practitioners, a number of statistically significant differences were revealed based on gender, spending habits, dining frequency, and prior food and beverage working experience. Research limitations/implications – The authors suggest an agenda for future academic research that will further clarify the dining habits of college students. Practice implications – The findings have a practical relevance to food and beverage marketers who wish to capture the attention of this significant market segment. The research recognised the market's potential, in addition of revealing major differences between college students in a number of dining-related factors with specific marketing implications. Originality/value – It is the first time that a scientific study has investigated college students' dining expectations in Cyprus. The results have practical implications for both academic scholars and food and beverage practitioners.
Keywords: Cyprus; Decision making; Restaurants; Students